STRATEGI PENINGKATAN MINAT MASYARAKAT TERHADAP LAYANAN PENGANTARAN OBAT (GOBAT) MELALUI PROMOSI EFEKTIF DI RSUD JENDERAL AHMAD YANI - Imelda, Riska; Lestari, Rizky Aprilianti; Pertiwi, Windi (Journal of Hospital Administration and Excellent Health Service, 2025)
Introduction: Long queues at outpatient pharmacies are a common complaint, prompting RSUD Jenderal Ahmad Yani Metro to launch the Home Drug Delivery (GOBAT) service to improve patient efficiency and comfort. This innovation aligns with the Minimum Service Standards for drug waiting times. However, the utilization rate of GOBAT is still not optimal. Method: This qualitative study involved data identification, problem identification, and root cause analysis using a Fishbone Diagram at RSUD Jenderal Ahmad Yani Metro. Result: The analysis revealed that a lack of promotion and information is the main reason for low public interest in GOBAT. Proposed innovations include X-banners, posters, and optimization of digital media through Instagram podcasts. Conclusion: Effective promotional strategies are expected to increase public awareness, understanding, and interest in GOBAT, contributing to improved hospital service efficiency.